The Role of Epistemic Modality in English Politeness Strategies - Carretero, Marta (Miscelánea: A Journal of English and American Studies, 1992)
The number of recent linguistics works on politeness has given evidence that this feature accounts for the way language is used to a greater extent than it would seem at first sight. This paper will prove the pervasive influence of politeness on epistemic modality, that is, the kind of modality which concerns judgements about the truth of the propositional content of an utterance. I shall adopt Brown and Levinson’s [1987] approach to politeness strategies in terms of ‘face’, ‘positive politeness’and ‘negative politeness’ —notions which will be made clear in the paper. The most obvious conclusions drawn from this analysis are 1) that expressions of uncertainty are used as politeness strategies both in directives (to soften the speaker’s imposition on the hearer), and in statements (to avoid full commitment to the truth of the proposition); and 2) that expressions which emphasize the speaker’s certainty about the truth of the proposition tend to highlight the speaker’s concern about the hearer’s wishes or interests. Nevertheless, this analysis does not exclude other frequent patterns of the use of epistemic expressions as politeness devices, such as the cases of apologies, answers to invitations, and contradictions.